OP0228 Protective Effect of LPA1 and 3 Receptor Antagonism in Experimental Skin Fibrosis is Linked to LPA Activity in Dermal Fibroblasts of SSC Patients. (23rd January 2014) - Illiano, S.; Ledein, L.; Bidouard, J.-P.; Schaefer, M.; Ruetten, H.; Janiak, P.; Beyer, C.; Distler, A.; Dees, C.; Distler, J. H.; Distler, O.
Abstract : Background: Lysophosphatidic acid (LPA) is a phospholipid generated by phospholipase D-mediated cleavage of phosphatidylcholine, mainly in adipocytes, fibroblasts or activated platelets. Knock down studies of the LPA1 receptor in lung and kidney fibrosis suggest a role of LPA in fibrosis. Objectives: To investigate the potential of LPA1/3 receptor antagonism in Systemic Sclerosis (SSc) using both in vitro and in vivo approaches. Methods: Primary cultures of dermal fibroblasts from patients with SSc and healthy controls were used for expression analysis and functional (Ca 2+ + cytokines measurement) in vitro studies (n=5 each). In some experiments, cells were pre-treated overnight with Pertussis Toxin (50 ng/ml) to evaluate Gi protein involvement in LPA-induced Ca 2+ response. The bleomycin skin model and the tight skin mouse model (Tsk-1) were used to assess the effects of the LPA1/3 antagonist SAR100842 (30 mg/kg BID) in vivo (n= 7 for each group) using established endpoints. Results: SSc skin fibroblasts expressed mainly LPA1 receptors and LPA4 receptors to a lower extent. The SSc fibroblasts demonstrated a greater sensitivity to LPA-induced increase in cytosolic Ca2+ than normal dermal fibroblasts. The LPA-induced increase in cytosolic Ca2+ was inhibited by Pertussis Toxin (supporting the evidence of a Gi coupling) and was also fully antagonized with SAR100842 (confirming the role of LPA1 receptors). LPA also induced expression of aSMA in SSc as well as markers of fibrosis like PAI-1, cytokines (IL-6, IL-8, CXCL-1, CCL-2) and markers of the Wnt pathway (SFRP4 and WNT2). In the mouse model of bleomycin-induced skin fibrosis, using a therapeutic protocol, LPA1/3 antagonism by SAR100842 reversed significantly (p<0.001) dermal thickness, inhibited myofibroblast differentiation and skin collagen content. These effects of SAR100842 were comparable to that of imatinib which was used as a positive control. In the Tsk-1 model, SAR100842 significantly decreased dermal thickness, myofibroblast differentiation and skin collagen content comparable with those obtained after treatment with imatinib (p < 0.05). In addition, SFRP4 and WNT2 gene expressions were also inhibited in the skin of TSK1 mice. Interestingly, the latter two markers were both induced by LPA in dermal fibroblasts from SSc patients and have been reported to be increased in the skin of SSc patients. SAR100842 also significantly (p<0.05) reduced the expression of IL-13, associated with the TH-2 cytokine milieu found in SSc, as well as CXCL-1. Conclusions: These results strongly implicate a role for LPA1 in the pathogenesis of skin manifestation of SSc and support the clinical development of SAR100842 in treating skin manifestation of SSc. Disclosure of Interest: S. Illiano Employee of: Sanofi, L. Ledein Employee of: Sanofi, J.-P. Bidouard Employee of: Sanofi, M. Schaefer Employee of: Sanofi, H. Ruetten Employee of: Sanofi, P. Janiak Employee of: Sanofi, C. Beyer: None Declared, A. Distler: None Declared, C. Dees: None Declared, J. Distler Shareholder of: 4 D Science, Consultant for: Boehringer Ingelheim, Celgene, Bayer Pharma, Actelion, Pfizer, Ergonex, BMS, JB Therapeutics, Anaphore, Inc, Sanofi-Aventis, Novartis, Array Biopharma and Active Biotec in the area of potential treatments of scleroderma, O. Distler Consultant for: Actelion, Pfizer, Ergonex, BMS, Sanofi-Aventis, United BioSource Corporation, Roche/Genentech, medac, Biovitrium, Boehringer Ingelheim Pharma, Novartis, 4 D Science, Active Biotec and Sinoxa in the area of systemic sclerosis and related conditions